"How" and "what" matters: Sampling method affects biodiversity estimates of reef fishes. Issue 13 (30th May 2017) - Bosch, Néstor E.; Gonçalves, Jorge M. S.; Erzini, Karim; Tuya, Fernando
Abstract: Understanding changes in biodiversity requires the implementation of monitoring programs encompassing different dimensions of biodiversity through varying sampling techniques. In this work, fish assemblages associated with the "outer" and "inner" sides of four marinas, two at the Canary Islands and two at southern Portugal, were investigated using three complementary sampling techniques: underwater visual censuses (UVCs), baited cameras (BCs), and fish traps (FTs). We firstly investigated the complementarity of these sampling methods to describe species composition. Then, we investigated differences in taxonomic (TD), phylogenetic (PD) and functional diversity (FD) between sides of the marinas according to each sampling method. Finally, we explored the applicability/reproducibility of each sampling technique to characterize fish assemblages according to these metrics of diversity. UVCs and BCs provided complementary information, in terms of the number and abundances of species, while FTs sampled a particular assemblage. Patterns of TD, PD, and FD between sides of the marinas varied depending on the sampling method. UVC was the most cost‐efficient technique, in terms of personnel hours, and it is recommended for local studies. However, for large‐scale studies, BCs are recommended, as it covers greater spatio‐temporal scales by a lower cost. Our study highlights the need to implement complementary sampling techniques to monitor ecological change, at various dimensions of biodiversity. The results presented here will be useful for optimizing future monitoring programs. Abstract : Different sampling methods to monitor reef fish assemblages produce varying patterns of taxonomic, phylogenetic, and functional diversity. It is recommended to implement various diversity metrics and complementary sampling techniques to assess the full range of species, phylogenies, and functional entities of reef fishes to properly inform conservation strategies.